Imaging Recommendations for Diagnosis, Staging, and Management of Uterine Cancer - Manchanda, Smita; Subashree, Anthoni Bala; Renganathan, Rupa; Popat, Palak Bhavesh; Dhamija, Ekta; Singhal, Seema; Bhatla, Neerja (Indian Journal of Medical and Paediatric Oncology, 2023)
Uterine cancers are classified into cancers of the corpus uteri (uterine carcinomas and carcinosarcoma) and corpus uteri (sarcomas) by the AJCC staging system (eighth edition). Endometrial carcinoma is the most common amongst these with prolonged estrogen exposure being a well-known risk factor. The FIGO staging system for endometrial carcinoma is primarily surgical and includes total hysterectomy, bilateral salpingo-oophorectomy, and lymphadenectomy. Imaging is useful in the preoperative evaluation of tumor stage, especially assessment of myometrial invasion and cervical stromal extension. Dynamic contrast enhanced MRI with DWI has a high staging accuracy and is the preferred imaging modality for primary evaluation with contrast-enhanced CT abdomen being indicated for recurrent disease. PET/CT is considered superior in evaluation of lymph nodes and extra pelvic metastases.
Keywords: dynamic contrast-enhanced MRI; endometrial neoplasms; gynecology and obstetrics; leiomyosarcoma; magnetic resonance imaging; medical oncology; positron emission tomography computed tomography; radiology